PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KINERJA GURU TERHADAP PRODUKTIVITAS SEKOLAH PADA SEKOLAH DASAR - Safaria, Veny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aimed to determine the effect: Whether the leadership of the principal and teacher performance affect the productivity of schools in public elementary schools?. This study uses a quantitative research approach. Data used is quantitative data. The research subjects were teachers in primary schools in the district of Sambas by the number of research subjects is 76 people. Hypothesis testing performed in this study using multiple regression techniques. the results of the analysis show that: (1) there is the influence of school leadership (X1) to the school productivity (Y) of 22.40%; (2) there is influence the performance of teachers (X2) on the school productivity (Y) of 60.40%; and (3) there is the influence of school leadership (X1) and the performance of teachers (X2) to the school productivity by 57.30%. He advised as follows: (1). principals must optimize leadership in order to improve achievement and teacher performance in the learning process to improve productivity of the school; (2) teachers improve the quality of the implementation process of learning that should be expected to increase the productivity of school Keywords: Leadership, Teacher Performance, Productivity School